2016
DOI: 10.1007/s12011-016-0824-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the EIF2α/ATF4 and ATF6 Pathways in DU-145 Cells by Boric Acid at the Concentration Reported in Men at the US Mean Boron Intake

Abstract: Fruits, nuts, legumes, and vegetables are rich sources of boron (B), an essential plant nutrient with chemopreventive properties. Blood boric acid (BA) levels reflect recent B intake, and men at the US mean intake have a reported non-fasting level of 10 μM. Treatment of DU-145 prostate cancer cells with physiological concentrations of BA inhibits cell proliferation without causing apoptosis and activates eukaryotic initiation factor 2 (eIF2α). EIF2α induces cell differentiation and protects cells by redirectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…Higher expression of HSP90B1 was associated with poor prognosis in non-small cell lung cancer patients[ 78 ] but the regulation of this gene during the progression of the prostate cancer is not yet known. There are, however, reports on how this gene is affected when the androgen-sensitive LNCaP and the androgen-insensitive prostate cancer cell lines are treated with androgen[ 79 ] or boric acid[ 80 ].…”
Section: Comparing Individual Genes In Two or More Phenotypesmentioning
confidence: 99%
“…Higher expression of HSP90B1 was associated with poor prognosis in non-small cell lung cancer patients[ 78 ] but the regulation of this gene during the progression of the prostate cancer is not yet known. There are, however, reports on how this gene is affected when the androgen-sensitive LNCaP and the androgen-insensitive prostate cancer cell lines are treated with androgen[ 79 ] or boric acid[ 80 ].…”
Section: Comparing Individual Genes In Two or More Phenotypesmentioning
confidence: 99%
“…Activating transcription factor 4 (ATF4) is the main component that encodes the cAMP response element-binding transcription factor, stimulating cell survival via modulation of redox reactions, stress response, protein synthesis, and secretion [ 62 , 63 ]. ATF4 is triggered by stress signals such as anoxia/hypoxia, amino acid abstinence, endoplasmic reticulum stress, and oxidative stress [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the toxic peptide, Aβ, induces ERS and then activates the unfolded protein response (8,13). It has been reported that ERS is involved in the cleavage of Aβ protein precursor, thus promoting the production of Aβ and facilitating the development of AD (1416). The results of the present study revealed that treatment with 20 mM Aβ 25-35 for 24 h contributed to the unbalancing of the redox state by reducing SOD activity, and increasing MDA content and ROS accumulation in PC12 cells, consistent with previous studies (17,18).…”
Section: Discussionmentioning
confidence: 99%